Awareness and Practice of Antimicrobial Stewardship Among Medical Students, Paramedical Students, and Paramedical Staff: A Cross-Sectional Study From Two Indian Medical Colleges - Hussain, Aqsa; Kaur, Arshpreet; Sardana, Madhav; Saha, Magnolia; Meena, Kanishka; Singhal, Harsh; Gupta, Utkarsh; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Antimicrobial resistance (AMR) poses a global threat to patient safety and healthcare quality. Antimicrobial stewardship (AMS) programs are essential to curb irrational prescribing and promote responsible antibiotic use. This study assesses the awareness and practice of AMS among medical students, nursing students, nurses, and technical staff in two tertiary care teaching hospitals. Methods: A cross-sectional survey was conducted among 250 participants: 100 MBBS students, 50 nursing students, and 100 nurses/technical staff. A validated Likert-scale questionnaire assessed knowledge, attitudes, and practices related to AMS. Descriptive statistics and chi-square tests were used to analyze group-wise differences. Results: MBBS students demonstrated higher awareness scores (mean ± SD: 4.2 ± 0.6) compared to nursing students (3.6 ± 0.7) and nurses/technical staff (3.4 ± 0.8). However, practical adherence to AMS protocols was suboptimal across all groups, with only 38% of nurses reporting routine use of hospital antibiograms. Significant gaps were noted in understanding of de-escalation strategies and documentation practices (p < 0.05). Conclusion: While awareness of AMS principles is moderate to high among students, practical implementation remains limited among paramedical staff. Targeted educational interventions and institutional support are crucial to strengthen AMS practices across healthcare cadres